Development of ambiguity aversion from early adolescence to adulthood: New insights from the Ellsberg paradox. (January 2023) - Osmont, Anaïs; Cassotti, Mathieu
This research aimed to clarify whether middle adolescents' risk-taking is driven by reduced ambiguity aversion. In Study 1, we explored the development of ambiguity aversion using an adaptation of the classic Ellsberg paradox with early adolescents (10–11 years old), middle adolescents (14–16 years old), and young adults (20–25 years old). Study 2 examined the development of ambiguity aversion depending on the ambiguity level in middle adolescence compared with adults. These two studies revealed that only early adolescents did not demonstrate ambiguity aversion. In contrast, middle adolescents and adults showed strong ambiguity aversion irrespective of ambiguity level. These findings support the idea that the period of young adolescence could be the start of ambiguity aversion development, although this tendency to avoid ambiguous options is already developed in middle adolescence. This finding might have important public health implications and suggests that prevention campaigns should consider early adolescence to be a particularly vulnerable age group for risky behaviors.